IV International Scientific Conference “Condensed Matter and Low Temperature Physics 2024” (CM&LTP 2024) Part II of the Special Issue (FNT/LTP No. 1, 2025) - Hurova, D.; Dolbin, O. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2025)
Part II of the Special Issue (Fizyka Nyzkykh Temperature/Low Temperature Physics, Vol. 51, No. 1, 2025) dedicated to the IV International Scientific Conference “Condensed Matter and Low Temperature Physics 2024” (CM&LTP 2024) presents papers that could not be included in the first part due to their volume and number